Maxims Deviation and Politeness Scale of Uang Panai Mahar Film by Using Leech's Perspective - Juflyn Alim; Hanip Pujiati; Siti Gomo Attas; Eva Leiliyanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The lack of knowledge about the application of maxims and politeness scale in everyday life cause more violation of politeness in communication. Speech deviations also occur in the Uang Panai Mahar film which raises the cultural theme of a moral message..This study aims to discuss and describe the maxims deviation and politeness conversation from film. The data of this study are the form of maxims deviation and politeness scale by using Leech perspective. The data source in this study is Uang Panai Mahar film, which published by Makita Cinema Production, on August 25, 2016. The film lasted for 1 hour, 59 minutes and 42 seconds. This study used descriptive qualitative method. This study found out some of maxims deviations and politeness scales, they were 1) deviation of wisdom, 2) deviation of generosity, 3) deviation of rewards, 4) deviation of simplicity, 5) deviation of accuracy and 6) deviation of sympathy. Meanwhile the politeness scale of this film were 1) the loss and gain scale, 2) the choice scale, 3) the sustainability scale and 4) social distance scale.